Profitability To Stock Returns - Widyakto, Adhi; Lestari, Rohmini Indah; Hanifah, Risti Ulfi (Journal of Economic Education, 2021)
The current growth of the capital market is accompanied by the growth of the stock market which continues to be in demand by investors as well, as can be seen from the information on the IDX which shows that stocks that are included in sharia are facing an increase. An investor wants to carry out analysis to make investment decisions. This analysis is technical in nature as well as fundamental. One of the fundamental analysis is the analysis of profitability ratios issued by the industry. Good monetary performance are going to be information that's used as a positive signal by investors, as a result of industries that have sensible financial performance can offer a lot of edges for investors. the aim of this analysis is to look at and analyze the profit variables of stock returns on the IDX for the 2016-2020 period. The population of this research is an industry listed on the IDX. This research uses illustration criteria, we get illustrations from 40 industries listed on the IDX for the 2016-2020 period and publish information on annual financial reports on the IDX that are needed throughout the research. The variables employed in this analysis are EPS, ROE, ROA, dimensions as management variables, and stock returns as the dependent variable. The results of this research show that investors in the Indonesia Stock Exchange (IDX) view the profitability ratio as a signal for making investment decisions. Variable dimensions may be used as management variables used in this analysis. Profitability ratios taken by investors are ROA, EPS. So it must be a special attention for industries